2021
DOI: 10.1021/acs.chemrev.1c00681
|View full text |Cite
|
Sign up to set email alerts
|

Deuteration for High-Resolution Detection of Protons in Protein Magic Angle Spinning (MAS) Solid-State NMR

Abstract: Proton detection developed in the last 20 years as the method of choice to study biomolecules in the solid state. In perdeuterated proteins, proton dipolar interactions are strongly attenuated, which allows yielding of high-resolution proton spectra. Perdeuteration and backsubstitution of exchangeable protons is essential if samples are rotated with MAS rotation frequencies below 60 kHz. Protonated samples can be investigated directly without spin dilution using proton detection methods in case the MAS frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 272 publications
(495 reference statements)
1
23
0
Order By: Relevance
“…The deuteration occurred at the position of carbon–bromine bonds in exclusive regioselectivity, which is in sharp contrast to the current methods for synthesizing deuterated aromatic compounds via C–H/C–D exchanges that often suffer from low regioselectivities. 37–44 Additionally, similar yields were obtained for the deuteration and hydrogenation of the same substrates, which suggests that the reaction was less susceptible to the kinetic isotope effect. For instance, 3,4-dicyanobromobenzene was converted into hydrogenation and deuteration products in 81% and 83% yields, respectively ( 2g and 2m ).…”
Section: Resultsmentioning
confidence: 58%
“…The deuteration occurred at the position of carbon–bromine bonds in exclusive regioselectivity, which is in sharp contrast to the current methods for synthesizing deuterated aromatic compounds via C–H/C–D exchanges that often suffer from low regioselectivities. 37–44 Additionally, similar yields were obtained for the deuteration and hydrogenation of the same substrates, which suggests that the reaction was less susceptible to the kinetic isotope effect. For instance, 3,4-dicyanobromobenzene was converted into hydrogenation and deuteration products in 81% and 83% yields, respectively ( 2g and 2m ).…”
Section: Resultsmentioning
confidence: 58%
“…The unsupervised PCA analysis results (Figure 5B) showed that the three toad venoms form separate clusters (R2X[1] = 46%, R2X[2] = 25.2%); the two clusters of Asiatic toad venom and spectacled toad venom are separated along PC1, whereas the cane toad venom is separated along PC2, indicating the significant variations in the bufadienolides among them. As indicated in the biplot (Figure S87) based on the PCA analysis, the key compounds contributing to the differentiation between the Asiatic toad and the other two were arenobufagin (7), cinobuotalin (15), and telocinobufagin (19), which had higher exposure in the Asiatic toad. Similarly, the chemicals 19-hydroxyl bufalin (24) and resibufogenin (22) were the reason for the clustering of spectacled toad samples, whereas mainobufagin (21) was the main chemical that distinguished the venom of cane toad from those of the other two toads.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, the analytical ability of traditional frequency-domain NMR using numerical integration in targeted metabolomics is still ineffective and might be only comparable to that of normal high-performance liquid chromatography (HPLC). Line fitting, 12 deconvolution, 13 novel pulse sequences, 14 and other methods 15 have been introduced to improve the resolution; however, these methods still could not meet the increasing analysis demand of high-throughput characteristics of targeted metabolomics due to the rather complicated resonance lines generated by varied complex samples. Normally, before frequency-domain NMR data can be investigated for metabolomics analysis, the raw data must be preprocessed, including baseline correction, phasing, apodization, referencing, and integration.…”
mentioning
confidence: 99%
“…In recent years, as the biophysical research toolbox expands rapidly, both in terms of technology and instrumentation, it has become very clear that deuteration of proteins and other biomolecular samples will greatly aid in high-quality outcomes for other biophysical applications, particularly small-angle neutron scattering (SANS) ( 14 , 15 , 16 , 17 ), pulsed double echo electron resonance (DEER) techniques ( 18 , 19 , 20 ), and neutron reflectometry ( 21 , 22 ). The general requirement is to effectively remove, or make nonresponsive, a component of the measurement as a result of perdeuteration, either through contrast matching as in SANS ( 23 ) or elongation of relaxation times via removal of dipolar coupling as in DEER and NMR ( 3 , 7 , 24 , 25 ). The SANS and NMR methods are further enhanced in the context of segmental labeling ( 26 , 27 , 28 , 29 ), wherein portions of a macromolecule may be prepared with deuteration for SANS (and/or isotopic labeling for NMR) and the other portions are protonated.…”
mentioning
confidence: 99%
“…Perdeuteration coupled with isotope labeling has been widely applied and greatly appreciated in the past 2 decades for protein NMR spectroscopy (1)(2)(3)(4)(5). Conventional NMR spectroscopy has benefited from uniformly labeled 15 N, 13 C protein samples, and, when these labeling patterns are combined with replacement of all nonexchangeable protons with deuterons to create a perdeuterated background, it is possible to study very large proteins and protein complexes (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%